Development of bio-based polymeric hydrogel: Green, sustainable and low cost plant fertilizer packaging material. Issue 1 (March 2016) - Ibrahim, Saber; Nawwar, Galal A.M.; Sultan, Maha
Graphical abstract: Highlights: Superabsorbent chicken gelatin-g-PAm copolymer packaging material. The optimum grafting degree was at acrylamide monomer/gelatin weight ratio 2:1. The highest swelling ratio was almost 8 times of its dry weight. Cumulative urea release exhibits Fickian mode. Increasing grafting degree enhance thermal stabilities of copolymer. Abstract: Low cost green fertilizer hydrogel packaging material was prepared based on waste chicken gelatin (WCG) using peroxy grafting copolymerization technique. Gelatin was grafted with acrylamide (AM) using ammonium persulphate (APS) as initiator. The effect of acrylamide concentration on grafting efficiency was studied. Highest grafting percentage of waste chicken gelatin (WCG-g-PAm) copolymers was detected at monomer ratio (Am 2:1 WCG). The non-protein nitrogen content, FT-IR, X-rays diffraction, and scanning electron microscope were determined as an evidence of grafting process. The swelling ratios, loading efficiency of urea on WCG-g-PAm copolymers in aqueous medium, and its slow release behavior were studied and quantized by spectroscopic methods. The solvent diffusion and behavior mechanism were studied. The results revealed that swelling and release behavior follow Fickian mechanism. Thermal analysis of WCG-g-PAm copolymers was applied to exhibit evidence on the grafting process. The thermal stability and total activation energies enhanced with increasing grafting degrees of WCG-g-PAm copolymers.